Self-Management Teaching as an Effort to Overcome Learning Loafing in PAI Lessons at SMKN 3 Palangka Raya - Anwar, Hadiya Sabila; Muslimah, Muslimah; Surawan, Surawan (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2025)
Self-management teaching as an effort to overcome the phenomenon of learning loafing among students, because learning loafing refers to students' unwillingness to actively engage in the learning process, which is often caused by a lack of motivation and effective self-management. Therefore, the purpose of this study is to find out the ways that teachers do in self-management teaching as an effort to overcome learning loafing in PAI learning. To achieve this goal, this study used a qualitative method with a phenomenological approach. The subjects of this study were PAI teachers and 10 students majoring in XI TKKR. Data were collected through observation, in-depth interviews with teachers and students, and documentation. The results showed that the application of self-management teaching by teachers at SMKN 3 Palangka Raya includes time management techniques, motivation development, and the creation of a supportive learning environment. Students involved in the self-management process showed an increase in learning engagement and achievement, as well as a decrease in lazy learning behavior. From these findings, it can be concluded that the implementation of self-management teaching can significantly reduce learning loafing and improve the quality of PAI learning.